1975
DOI: 10.1128/jb.124.1.112-118.1975
|View full text |Cite
|
Sign up to set email alerts
|

Maltose transport in Escherichia coli K-12: involvement of the bacteriophage lambda receptor

Abstract: Mutants affected in lamB, the structural gene for phage lambda receptor, are unable to utilize maltose when it is present at low concentrations (less than or equal 10 muM). During growth in a chemostat at limiting maltose concentrations, the lamB mutants tested were selected against in the presence of the wild-type strain. Transport studies demonstrate that most lamB mutants have deficient maltose transport capacities at low maltose concentrations. When antibodies against purified phage lambda receptor are add… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
157
0
1

Year Published

1980
1980
2008
2008

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 302 publications
(160 citation statements)
references
References 17 publications
2
157
0
1
Order By: Relevance
“…The following hypothesis might explain why the combined cost of resistance in E. coli to viruses T4 and A is less than expected from the separate costs for each virus alone, especially in trehalose. Mutations that confer resistance to A usually cause loss or structural modification of the LamB protein, the outer membrane receptor to which A initially binds to the bacterial cell (Szmelcman and Hofnung 1975;Arber 1983). LamB is involved in the uptake of maltose and trehalose, but not glucose (Klein and Boos 1993;Travisano and Lenski 1996).…”
Section: Discussionmentioning
confidence: 99%
“…The following hypothesis might explain why the combined cost of resistance in E. coli to viruses T4 and A is less than expected from the separate costs for each virus alone, especially in trehalose. Mutations that confer resistance to A usually cause loss or structural modification of the LamB protein, the outer membrane receptor to which A initially binds to the bacterial cell (Szmelcman and Hofnung 1975;Arber 1983). LamB is involved in the uptake of maltose and trehalose, but not glucose (Klein and Boos 1993;Travisano and Lenski 1996).…”
Section: Discussionmentioning
confidence: 99%
“…Among them, a small number convey selective permeability to compounds larger than the exclusion size. One of them is induced by growth on maltose (Szmelcman and Hofnung, 1975), and allows growth at low concentrations of maltose or in the presence of maltose oligomers. Thus, maltodextrins up to the size of maltoheptaose, a compound well above the apparent pore size, are transported into cells Nakae and Ishii, 1980).…”
Section: Introductionmentioning
confidence: 99%
“…In vivo, Escherichia coli takes up maltose by the sequential action of several proteins encoded in the maltose B operon (Hofnung, 1974). Transport substrates diffuse into the peripplasmic space through the channels formed by maltoporin (Szmelcman and Hofnung, 1975). They are then bound to the soluble maltose-binding protein (Kellermann and Szmelcman, 1974) which delivers the sugar to the system which actively transports it across the cytoplasmic membrane (Shuman et al, 1980).…”
mentioning
confidence: 99%
“…Their relative amounts are determined by the osmotic pressure of the growth medium (van Alphen and Lugtenberg, 1977). The synthesis of PhoE protein is induced when cells are growing under (c)IRL Press Limited, Oxford, England phosphate limitation (Overbeeke and Lugtenberg, 1980) while LamB protein is induced by the presence of maltose (Szmelcman and Hofnung, 1975). Nucleotide sequence analysis of the ompF, ompC, phoE genes (Inokuchi et al, 1982;Mizuno et al, 1983) has revealed an extensive homology of -60% in the primary structures of these three proteins while LamB protein is apparently unrelated to the other porins (Clement and Hofnung, 1981).…”
mentioning
confidence: 99%